2000
DOI: 10.1002/1097-0142(20001115)89:10<2099::aid-cncr10>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

A combination therapy of continuous superselective intraarterial carboplatin infusion and radiation therapy for locally advanced head and neck carcinoma

Abstract: Superselective continuous intraarterial carboplatin and concurrent radiation therapy can be delivered safely with good efficacy for locally advanced carcinomas of the tongue and base of the tongue. Surgical treatment of these diseases usually incurs severe functional loss. This current approach may be a breakthrough in these cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…As previously reported (Fuwa et al, 2000), the anterior ear on the affected side was incised under local anaesthesia to expose the superficial temporal artery. During fluoroscopy, a thin catheter was selectively inserted into the selected artery.…”
Section: Arterial Injection Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported (Fuwa et al, 2000), the anterior ear on the affected side was incised under local anaesthesia to expose the superficial temporal artery. During fluoroscopy, a thin catheter was selectively inserted into the selected artery.…”
Section: Arterial Injection Therapymentioning
confidence: 99%
“…In 1992, we started chemoradiation therapy, in which continuous arterial infusion therapy with carboplatin was combined with radiotherapy, by selectively inserting a catheter into the target artery through the superficial temporal artery in patients with locally advanced head and neck cancer (Fuwa et al, 2000). We started therapy in two courses of systemic chemotherapy combined with intra-arterial chemoradiotherapy by continuous intra-arterial infusion of carboplatin and radiation therapy, in an effort to control metastasis in cervical lymph nodes and distant metastasis in 1997 (Fuwa et al, 2007).…”
mentioning
confidence: 99%
“…Mainly, it was used in concurrent combination with radiation (Robbins et al, 1994;Shibuya et al, 1994;von Scheel et al, 1996;Fuwa et al, 2000;Furutani et al, 2002;Yamashita et al, 2002;Kitagawa et al, 2003) or alone (Nakasato et al, 2000). The drugs used mainly have been cisplatin or carboplatin.…”
mentioning
confidence: 99%
“…The drugs used mainly have been cisplatin or carboplatin. Administration was either continuously over a temporal retrograde approach (Fuwa et al, 2000;Nakasato et al, 2000;Furutani et al, 2002) or by repeated bolus infusions over a transfemoral anterograde approach (Robbins et al, 1994). The temporal approach had the general disadvantage of not being selective or superselective.…”
mentioning
confidence: 99%
“…The knowledge of such arterial variation is useful during intra-arterial chemotherapy for the treatment of tongue cancers, musculomucosal island flap for partial tongue reconstruction, superselective intraarterial chemotherapy for head and neck carcinomas, these variations should be kept in mind [5,8,[12][13][14]. Zumre et al [5] observed thyrolingual trunk in 2.5% and thyrolinguofacial trunk in 2.5% of the cases in human foetuses.…”
Section: Discussionmentioning
confidence: 99%